Plan de marketing para la panadería K-RU-K ubicada en Ciénaga - Magdalena (2023)
This research project is called Marketing Plan for the K-RU-K Bakery located in Ciénaga, Magdalena. This was carried out taking into account the market, therefore, different investigations were carried out which helped to obtain the data with which different observations and recommendations could be made. One of the strategies that were addressed in this work was the development of a market research because the customer plays a key role in these businesses where competitiveness is very high and the implementation of the 4p's of marketing where specific recommendations are made based on an analysis made in order to achieve a high management and to generate greater competitiveness in terms of other local sector. Some of the recommendations made in the sections were, in plaza, which was the remodeling of the visual section of the same so that it adapts more to the needs or desires of consumers; in promotion, the OTL strategy was implemented which is based on advertising through the Internet; in person, the realization of talks or training with employees every 3 or 4 months in order to emphasize the importance of different sections such as teamwork and customer service; and finally in price, where it is sought that customers see greater importance to quality over price. Some of the subjects that helped in the elaboration of this research were: Probability and statistics, applied statistics and marketing.